A Comparative Study of Beliefs in Islam and Zoroastrianism - Alizah Sadaf (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2022)
Zoroastrianism is one of the oldest religions in the world. Islam is a major religion of the world. Both Islam and Zoroastrianism are monotheistic religions. However, both of them are different. Both the religions have different beliefs, set of values, customs, holy book and holy prophet. Even their concept of God is quite far apart. We look around us and some questions pop in our mind. Who created this world, the sky, space, sun, trees, clouds, seas, oceans, and mountains. Who created humans and other living creatures? All these questions lead us to believe that there is an entity a power behind all this, who has created everything. This entity became known as God. Scholars all over the world study and carry research on these two religions. Islam teaches us to believe in one and only God “Allah” whereas in Zoroastrianism in the guise of God a dualistic belief is there. This dualistic belief has been studied very thoroughly by experts and religious scholars. The major beliefs and thoughts and developments in Islam and Zoroastrianism would be discussed here in the light of evidence from various articles. How both the religions influence each other and what are both their perspectives on each other and their ideologies? All these factors would be discussed in this article.